E-Logbook Laporkan Kondisi Kesehatan, Absen & Kinerja Dosen, Kependidikan dan Kontrak selama WFH - Roni Putra; Ronal Hadi; Hidra Amnur; Dedy Prayama; Rita Afyeni; Anggara Nasution (SOTVI - Society of Visual Informatics, 2021)
There are 210 countries / regions infected with the corona virus, the corona virus has now infected at least 2,197,968 people in the world. Meanwhile, Indonesia occupies the 36th position with a total of 5,923 cases. A total of 520 people died and 607 others recovered. Starting from the conditions currently developing in connection with the spread of the covid-19 virus, the WFH (Work from Home) program was launched. This is intended to break the chain of spreading the virus. As a consequence of the implementation of these activities, all activities that lead to the gathering of large numbers of people, such as lectures at the Padang State Polytechnic campus, are temporarily suspended for an unclear time. This is based on the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07 / MENKES / 260/2020 concerning Stipulation of Large-Scale Social Restrictions in the Region of West Sumatra Province in the Context of Accelerating Handling of Corona Virus Disease 2019 (Covid-19). This decision, he continued, has been followed up by the issuance of West Sumatra Governor Regulation Number 20 of 2020 concerning Guidelines for Large-Scale Social Restrictions in Handling Corona Virus Disease 2019 (Covid-19) in West Sumatra Province and West Sumatra Governor Decree Number 180-297-2020 concerning Enforcement of Large-Scale Social Restrictions in the West Sumatra Province in the Context of Accelerating Handling of Corona Virus Disease 2019 (Covid-19). Circular of the Secretary General of the Ministry of Education and Culture Number 36604 / A3 / KP / 2020 dated March 15, 2020 concerning Procedures for Employees Working from Home and Deputy Director II of Padang State Polytechnic Number: 653 / PL9 / KP / 2020, March 26, 2020 concerning Work Notices from home or Work From Home (WFH). Lecturers, education personnel and honorary staff are encouraged to report their health, attendance and occupation through a certain application. Seeing the current needs and conditions, the Team took the initiative to make an application referred to as a quick and precise solution according to current conditions and in accordance with the regulations issued by the center up to the Padang State Polytechnic. The goal to be achieved from this service activity is to be able to help facilitate WFH reports through an E-logbook application in conditions that are not conducive to the covid-19 outbreak and participate in supporting government programs for better WFH because the information is well stored